Polymeric AIE-based nanoprobes for biomedical applications: recent advances and perspectives. Issue 27 (26th May 2015) - Zhang, Xiaoyong; Wang, Ke; Liu, Meiying; Zhang, Xiqi; Tao, Lei; Chen, Yiwang; Wei, Yen
Abstract : The recent advances and prospects of polymeric AIE dye-based nanoprobes for biomedical applications are summarized in this review article. Abstract : The development of polymeric luminescent nanomaterials for biomedical applications has recently attracted a large amount of attention due to the remarkable advantages of these materials compared with small organic dyes and fluorescent inorganic nanomaterials. Among these polymeric luminescent nanomaterials, polymeric luminescent nanomaterials based on dyes with aggregation-induced emission (AIE) properties should be of great research interest due to their unique AIE properties, the designability of polymers and their multifunctional potential. In this review, the recent advances in the design and biomedical applications of polymeric luminescent nanomaterials based on AIE dyes is summarized. Various design strategies for incorporation of these AIE dyes into polymeric systems are included. The potential biomedical applications such as biological imaging, and use in biological sensors and theranostic systems of these polymeric AIE-based nanomaterials have also been highlighted. We trust this review will attract significant interest from scientists from different research fields in chemistry, materials, biology and interdisciplinary areas.